Implementasi Kebijakan Pembebasan/Penghapusan Sanksi Denda Pajak Kendaraan Bermotor (PKB) di Kota Pekanbaru - Tommy Pratama; Harapan Tua RFS (Peneliti.net, 2022)
This study aims to determine the Implementation of the Motor Vehicle Tax Administration (PKB) Exemption/Elimination Policy in Pekanbaru City using the theory of Policy Implementation according to George Edward III, namely communication, resources, dispositions, and bureaucratic structures. This type of research is qualitative which is descriptive with data collection techniques are interviews, observations, and documentation. For the determination of the informant, the author used purposive sampling. Furthermore, to analyze the data obtained, the author used an interactive analysis model from Soegiyono. The results showed that the implementation of the Motor Vehicle Tax Administration Sanctions Exemption/Elimination Policy (PKB) in Pekanbaru City has not gone well which can be seen from all the indicators used in this study. Factors that become obstacles in the implementation of the Policy of Exemption / Elimination of Motor Vehicle Tax Fines (PKB) in Pekanbaru City are the lack of socialization carried out by the Riau Provincial Bapenda to taxpayers and the lack of discipline of existing employees.